Long-term population dynamics and seasonal development of the Colorado potato beetle on potato plantings in the Leningrad region under conditions of climate warming - V. V. Smuk (Аграрная наука Евро-Северо-Востока, 2024)
The Colorado potato beetle (Leptinotarsa decemlineata Say) is the main and most dangerous pest of potatoes in Russia. Having wide adaptive capabilities, this species is gradually acclimatizing in the more northern regions of the territory of the Russian Federation. The Northwestern region has so far been considered an area with unfavorable conditions for the development of the Colorado potato beetle, but in a warming climate, the situation may change significantly. In the period of 2012–2023, field experiments conducted at the agroecological study area of the Menkovsky branch of the Agrophysical Research Institute (Leningrad region, Gatchina district) studied the long-term population dynamics and seasonal development of the Colorado potato beetle on potato plantings under conditions of different heat supply in the summer months. According to the research results, a rapid increase (from 0.1 to 68 % of plants at the time of «budding-flowering») in the presence of phytophage in the potato agrocenosis was revealed, due to a prolonged (2021–2023) significant increase in the sum of active temperatures during the growing season of the crop. The opposite effect was observed at low air temperature in the second and third decades of June. A decrease in heat supply in these decades below the temperature optimum led to a decrease in the average number of eggs in a clutch from 37 to 22 and a shift in the mass hatching of larvae to later periods (over 7 days) of the growing season of the crop. The seasonal dynamics of insect numbers is characterized by a sharp decrease in the density of phytophagous larvae after budding of potato plants. The determining factor in the mass development of the Colorado potato beetle in potato plantings is the high number of the insect at the initial stage of colonization of the potato field. Thus, with a multiple (3.7 times) excess of the economic threshold of harmfulness according to the criterion of the number of overwintered imago of the Colorado potato beetle in the phase of mass shoots of the crop, a high level (90–100 %) of plant damage by larvae was observed in the second half of the potato growing season.